HUKUM JUAL BELI TAWARRUQ MENURUT IBNU TAIMIYAH - Bin Azman, Ahmad Fathi Aiman; Ibrahim, Duski; Isa, Muhammad Legawan (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
In Islamic banking, the sale and purchase of tawarruq is increasingly being used in the product structure of deposits, financing, asset management and risk coverage. Even so, the general public still does not know about the existence of the sale and purchase of tawarruq, and there are even people who know about its existence but do not understand the sale and purchase of the bargain in terms of understanding and implementation. The sale and purchase of this tawarruq is a sale and purchase that has been agreed upon by the jumhur ulama that its practice is permitted in fiqh mu'amalah. However, Ibn Taymiyyah prohibited the sale and purchase of this offering. The purpose of this research is to find out the essence in more detail about the meaning of the sale and purchase of bargains both in terms of language and terms according to what has been proposed by the scholars, scientists and Ibn Taymiyyah as well as to know the law of the sale and purchase of bargains according to Ibn Taymiyyah. This research method is a research library with a qualitative approach consisting of primary, secondary and tertiary data. The data collection technique used descriptive analysis and synthesis analysis methods. By presenting first the data regarding the theories about the concept of the concept of tawarruq, as well as the views of the scholars regarding the concept of bargaining and Ibn Taymiyyah prohibitions against the concept of tawarruq then analyzed in narrative form. The results of the study show that the meaning of the sale and purchase of tawarruq in general is when someone who needs money and does not get someone who can provide a loan, then buys goods to someone on credit and resells them in cash to a third party with the intention of getting money or capital , then take advantage of the sales. Ibn Taymiyyah stated that the law of the sale and purchase of tawarruq was makruh. Keywords: Tawarruq, Fiqih Mu'amalah, Jumhur Ulama, Makruh.